Perbandingan Hasil Belajar Siswa Antara Model Pembelajaran Kooperatif Tipe Jigsaw Dengan Pembelajaran Konvensional Pada Mata Pelajaran Dasar-dasar Elektronika Kelas X SMK Negeri 2 Solok - Adlian Jefiza; Hanesman Hanesman; Zulhendra Zulhendra (Universitas Negeri Padang, 2014)
The purpose of this study is to compare students learning outcomes between using jigsaw cooperative models with conventional learning on electronics basic subject in students class X of SMK Negeri 2 Solok . this research is experimental research that aims to reveal differences in students learning outcomes using cooperative learning jigsaw ( X1 ) and Conventional Learning ( X2) on students learning outcomes ( Y ) . The population is 61 person tenth grade students enrolled TAV SMF SMK 2 TP.2013/2014. The results of the research analysis , student learning outcomes in the experimental group using the model of cooperative jigsaw have an average score ( 79.47 ) higher than students learning outcomes in control group using conventional methods have an average score ( 68.27 ) , where the learning outcomes of students in experimental class had above the average standard of completeness . While the t - test is 4.09. Thus, the previous alternative hypothesis can be accepted at 95 % of significant level. There is a significant difference in students learning outcomes between the use of cooperative learning model jigsaw with conventional models in electronics basic subject of stuydents grade X in SMKN 2 Solok Keywords : differences , jigsaw , conventional , learning outcomes